Assessing societal and offender perspectives on the value of offender healthcare: a stated preference research protocol. Issue 3 (23rd March 2019) - Settumba, Stella Nalukwago; Shanahan, Marian; Chambers, Georgina, M; Schofield, Peter; Butler, Tony
Abstract : Introduction: The increasing burden that offenders place on justice and health budgets necessitates better methods to determine the benefits of and value society places on offender programmes to guide policy regarding resource allocation. The aim of this paper is to demonstrate how economic methods will be used to determine the strength of preferences and value of violent offender treatment programmes from the perspectives of offenders, their families and the general population. Methods and analysis: Two stated preference economic methods, discrete choice experiment (DCE) and contingent valuation (CV), will be used to assess society's and offenders' value of treatment programmes. The mixed methods process involves a literature review and qualitative methods to derive attributes and levels for the DCE and payment card values for the CV. Consensus building approaches of voting, ranking and the Delphi method will be used to further refine the findings from the qualitative phase. Attributes and their levels will be used in a D-efficient Bayesian experimental design to derive choice scenarios for the development of a questionnaire that will also include CV questions. Finally, quantitative surveys to assess societal preferences and value in terms of willingness to pay will be conducted. Ethics and dissemination: Ethics approval for this study was obtained from the University of New South Wales (UNSW) Human Research Ethics Committee, Corrective Services New South Wales Ethics Committee and the Aboriginal Health and Medical Research Council ethics committee. The findings will be made available on the Kirby Institute UNSW website, published in peer-reviewed journals and presented at national and international conferences.